1989
DOI: 10.1042/bj2640475
|View full text |Cite
|
Sign up to set email alerts
|

The specificity of bovine spleen cathepsin S. A comparison with rat liver cathepsins L and B

Abstract: The peptide-bond-specificity of bovine spleen cathepsin S in the cleavage of the oxidized insulin B-chain and peptide methylcoumarylamide substrates was investigated and the results are compared with those obtained with rat liver cathepsins L and B. Major cleavage sites in the oxidized insulin B-chain generated by cathepsin S are the bonds Glu13-Ala14, Leu17-Val18 and Phe23-Tyr26; minor cleavage sites are the bonds Asn3-Gln4, Ser9-His10 and Leu15-Tyr16. The bond-specificity of this proteinase is in part simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
69
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(82 citation statements)
references
References 25 publications
12
69
0
Order By: Relevance
“…3E). Similar P 2 specificity for hydrophobic residues has been observed in single substrate studies for bovine and human cathepsin S (58,71). The diminished acceptance of P 2 Val residues relative to cathepsin V and cathepsin L may be attributed to the presence of a Val residue that more greatly restricts the entrance to the S 2 pocket in cathepsin S relative to cathepsin V (which contains a Leu residue at this position) and Cat L (which has a Met residue at this position).…”
Section: Resultsmentioning
confidence: 51%
“…3E). Similar P 2 specificity for hydrophobic residues has been observed in single substrate studies for bovine and human cathepsin S (58,71). The diminished acceptance of P 2 Val residues relative to cathepsin V and cathepsin L may be attributed to the presence of a Val residue that more greatly restricts the entrance to the S 2 pocket in cathepsin S relative to cathepsin V (which contains a Leu residue at this position) and Cat L (which has a Met residue at this position).…”
Section: Resultsmentioning
confidence: 51%
“…Both the F: hepatica cathepsins L1 and L2 have a high affintiy (k,,, /Km) for the substrate Z-Phe-Arg-NHMec and low affinity for the substrates Z-Arg-Arg-NHMec and Bz-ArgNHMec. The preference for a hydrophobic phenylalanine residue in the P2 position is consistent with the classification of both I;: hepatica proteinases as cathepsin L species [2] or cathepsin S proteases [26,271. Both enzymes, however, have a threefold greater affinity for the substrate Boc-Val-LeuLys-NHMec over the substrate Z-Phe-Arg-NHMec ; the cathepsin L2 has greater than twice the affinity for these two substrates when compared to the cathepsin L1.…”
Section: Kinetic Studies Of E Hepatica Cathepsins L1 and L2supporting
confidence: 54%
“…Bromme et al [26] showed that bovine cathepsin L had a tenfold preference for the substrate Z-Phe-Arg-NHMec Other strips were incubated in 10 pM fluorogenic peptide substrate. The substrates used were, Z-Phe-Arg-NHMec (FR) ; Boc-Val-LeuLys-NHMec (VLK); Tos-Gly-Pro-Arg-NHMec (GPR) and Tos-GlyPro-Lys-NHMec (GPK).…”
Section: Kinetic Studies Of E Hepatica Cathepsins L1 and L2mentioning
confidence: 99%
“…According to previously reported studies, the specificity of CatS is mainly determined by the amino acid at the P-2 position (9,(32)(33)(34). In those studies, conclusions on the CatS specificity were often drawn from the cleavage of fluorogenic substrates containing the fluorophore at the P-1Ј position.…”
Section: Discussionmentioning
confidence: 99%